2005
DOI: 10.1093/aje/kwi121
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P-450 1A1 Gene Polymorphisms and Risk of Breast Cancer: A HuGE Review

Abstract: Cytochrome P-450 (CYP) 1A1 plays a key role in phase I metabolism of polycyclic aromatic hydrocarbons and in estrogen metabolism. It is expressed predominantly in extrahepatic tissues, including the breast. Four CYP1A1 gene polymorphisms (3801T --> C, Ile462Val, 3205T --> C, and Thr461Asp) have been studied in relation to breast cancer. The 3801C variant is more common than the Val variant. Both variants occur more frequently in Asians than in White populations. The 3205T --> C polymorphism has been observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 202 publications
8
86
0
Order By: Relevance
“…The two polymorphisms have not been shown to be in linkage disequilibrium [35]. The CYP1A1 Thr 461 Asn SNP has not been associated with lung cancer [35] or breast cancer [34,36] in casecontrol studies. After a review of sequence data from 130 individuals, we found 5 instances (3.3%) where the second SNP was heterozygous; however, in each case the Ile 462 Val locus was homozygous and the call was not affected by the other SNP.…”
Section: Discussionmentioning
confidence: 99%
“…The two polymorphisms have not been shown to be in linkage disequilibrium [35]. The CYP1A1 Thr 461 Asn SNP has not been associated with lung cancer [35] or breast cancer [34,36] in casecontrol studies. After a review of sequence data from 130 individuals, we found 5 instances (3.3%) where the second SNP was heterozygous; however, in each case the Ile 462 Val locus was homozygous and the call was not affected by the other SNP.…”
Section: Discussionmentioning
confidence: 99%
“…Two mutually linked polymorphisms of the human CYP1A1 gene, the MspI polymorphism (*2A) located in the 3'-flanking region of the gene and the Ile-Val polymorphism (*2B) at amino acid residue 462 in the haeme-binding region, were reported to be associated with susceptibility to tobacco smoking-associated squamous-cell carcinoma of the lung in Japanese populations Kawajiri & Fujii-Kuriyama, 1991;Nakachi et al, 1993;Kawajiri et al, 1996;Masson et al, 2005). However, this association has not been found in other ethnic groups (Tefre et al, 1991;Hirvonen et al, 1992).…”
Section: (I)mentioning
confidence: 99%
“…Individuals have different and unique combinations of drug-metabolizing enzymes in their organs (Nebert et al, 1999;Daly, 2003). For example, some people have enzymes that are defective for the activation of PAHs and normal enzymes that detoxicate PAHs, whereas others have normal enzymes that activate PAHs and enzymes that are defective for the detoxication of reactive PAH metabolites (Garte et al, 2001;Murata et al, 2001;Yin et al, 2001;Kiyohara et al, 2002a;Hung et al, 2004;Lodovici et al, 2004;Masson et al, 2005). In these cases, it is difficult to interpret from epidemiological studies which polymorphisms of drug-metabolizing enzymes are involved in susceptibility to human cancer.…”
Section: (Iv) Evidence For Diol Epoxide Metabolic Activation As a Mecmentioning
confidence: 99%
See 1 more Smart Citation
“…The CYP1A1 gene, located at 15q22-q24, comprises seven exons and six introns and spans 5,810 base pairs (Masson et al, 2005). CYP1A1 enzyme belong to cytochrome p450 family, and responsible for the activation of procarcinogens to reactive metabolites (Turesky and Le Marchand, 2011) CYP isoforms metabolize estrogens to catecholoestrogens (CEs), semiquinones and quinines by oxidation reactions.…”
Section: Introductionmentioning
confidence: 99%